2021
DOI: 10.3390/membranes11110850
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Asymmetric Mesoporous PTFE/Clay Composite Membranes for Textile Wastewater Treatment

Abstract: Asymmetric mesoporous composite PTFE membranes wit 40, 50, and 85 wt.% of a clay (kaolin) were fabricated and characterized using a scanning electron microscope equipped with EDX for morphology and elemental analysis. The surface chemistry of the membranes was checked using Fourier transform infrared spectroscopy. The effect of incorporating the clay on the hydrophilicity, permeability, morphology, and antifouling properties of the fabricated membranes was investigated. It was observed that incorporating kaoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…The image shows that the aggregated particles were evenly distributed with the formation of pores, revealing the ability to dissolve in lubricant, while the EC-CMC sample had a gel-like appearance. The observations are in consonant with previous reports 13,14. The energy-dispersive X-ray (EDX) analysis is shown in Table1, revealing the presence of many elements in EC-CMC while only carbon and fluorine whereas the Zr element was from the coating process.…”
supporting
confidence: 91%
“…The image shows that the aggregated particles were evenly distributed with the formation of pores, revealing the ability to dissolve in lubricant, while the EC-CMC sample had a gel-like appearance. The observations are in consonant with previous reports 13,14. The energy-dispersive X-ray (EDX) analysis is shown in Table1, revealing the presence of many elements in EC-CMC while only carbon and fluorine whereas the Zr element was from the coating process.…”
supporting
confidence: 91%
“…Furthermore, several studies have shown that the ceramic/PTFE blend provides a porous structure composed of nodes connected by fibrils as revealed in the SEM images of our membrane. Similarly, Bousbih et al [30] reported that the formation of a porous structure is due to the penetration of PTFE polymer between the ceramic layers. and a high percolation threshold.…”
Section: Morphologymentioning
confidence: 90%
“…For the evaluation of UF rejection, the rejection of different parameters (COD, turbidity, oil, and heavy metals) was determined by Equation (2) [50,51]:…”
Section: Methodsmentioning
confidence: 99%
“…For the evaluation of UF rejection, the rejection of different parameters (COD, turbidity, oil, and heavy metals) was determined by Equation (2) [ 50 , 51 ]: where C f and C p represent the concentration of pollutants in the feed and in the permeate, respectively.…”
Section: Methodsmentioning
confidence: 99%